The Influence of Lifestyle Modifications in Elderly People With Hypertension on Self-Efficacy and Quality of Life - Resnayati, Yeti; Maryam, Raden Siti; Riasmini, Ni Made; Pudjiati, Pudjiati; Carolina Hapsari, Dina (Nursing Genius Journal, 2024)
Background:  Problems in the elderly occur due to a decline in all organ functions. The aging process can cause various physical, biological, mental, and socio-economic problems. One very important factor influencing quality of life is lifestyle and lifestyle promotion behavior.  Methods:  Pretest-posttest research design with control group design. Sample of elderly individuals. The sampling strategy used was simple random sampling with a sample size of 39 each for the intervention group and control group. Data analysis used the difference between two means test (t-test). Results:   shows a significant difference (p = 0.000) in self-efficacy and quality of life for the elderly between the intervention group and the control group after the lifestyle modification intervention. Conclusion:    It is hoped that continued promotional and preventive activities for senior people can be carried out through the integrated guide post (Posbindu). Lifestyle adjustments for elderly people with hypertension can increase their self-efficacy and quality of life.